Особистісні особливості підлітків із нормативною і девіантною поведінкою - Кірейчев, Андрій (Видавництво Львівської політехніки, 2012)
В статье проведен анализ психолого-педагогической литературы по проблеме девиантного поведения подростков. Обобщены результаты изучения типичных и специфических личностных черт младших подростков с нормативным и девиантным поведением. Article analyses the psychological and pedagogical literature on the problem of adolescents’ deviant behavior. The author summarizes the results of the study of typical and specific personality traits of junior adolescents with normative and deviant behavior.
Личностные особенности подростков c нормативным и девиантным поведением
Personal peculiarities of adolescents with normative and deviant behavior
Keywords: девиантное поведение; делинквентное поведение; агрессивность; тревожность; локус контроля; deviant behavior; delinquent behavior; aggressiveness; anxiety; locus of control